Fear influences phantom sound percepts in an anechoic room - Denys, Sam; Cima, Rilana F. F.; Fuller, Thomas E.; Ceresa, An-Sofie; Blockmans, Lauren; Vlaeyen, Johan W. S.; Verhaert, Nicolas (Frontiers in Psychology, 2022)
Aims and hypotheses In an environment of absolute silence, researchers have found many of their participants to perceive phantom sounds (tinnitus). With this between-subject experiment, we aimed to elaborate on these research findings, and specifically investigated whether–in line with the fear-avoidance model of tinnitus perception and reactivity–fear or level of perceived threat influences the incidence and perceptual qualities of phantom sound percepts in an anechoic room. We investigated the potential role of individual differences in anxiety, negative affect, noise sensitivity and subclinical hearing loss. We hypothesized that participants who experience a higher level of threat would direct their attention more to the auditory system, leading to the perception of tinnitus-like sounds, which would otherwise be subaudible, and that under conditions of increased threat, narrowing of attention would lead to perceptual distortions. Methods In total, N = 78 normal-hearing volunteers participated in this study. In general, the study sample consisted of young, mostly female, university students. Their hearing was evaluated using gold-standard pure tone audiometry and a speech-in-noise self-test (Digit Triplet Test), which is a sensitive screening test to identify subclinical hearing loss. Prior to a four-minute stay in an anechoic room, we randomized participants block design-wise in a threat (N = 37) and no-threat condition (N = 41). Participants in the threat condition were deceived about their hearing and were led to believe that staying in the room would potentially harm their hearing temporarily. Participants were asked whether they perceived sounds during their stay in the room and rated the perceptual qualities of sound percepts (loudness and unpleasantness). They were also asked to fill-out standardized questionnaires measuring anxiety (State–Trait Anxiety Inventory), affect (Positive and Negative Affect Schedule) and noise sensitivity (Weinstein Noise Sensitivity Scale). The internal consistency of the questionnaires used was verified in our study sample and ranged between α = 0.61 and α = 0.90. Results In line with incidence rates reported in the literature, 74% of our participants reported having heard tinnitus-like sounds in the anechoic room. Speech-in-noise identification ability was comparable for both groups of participants. The experimental manipulation of threat was proven to be effective, as indicated by significantly higher scores on a Threat Manipulation Checklist among participants in the threat condition as compared to those in the no-threat condition (p < 0.01). Nevertheless, participants in the threat condition were as likely to report tinnitus percepts as participants in the no-threat condition (p = 1), and tinnitus percepts were not rated as being louder (p = 0.76) or more unpleasant (p = 0.64) as a function of level of threat. For participants who did experience tinnitus percepts, a higher level of threat was associated with a higher degree of experienced unpleasantness (p < 0.01). These associations were absent in those who did not experience tinnitus. Higher negative affect was only slightly associated with higher ratings of tinnitus unpleasantness (p < 0.01). Conclusion Whereas our threat manipulation was successful in elevating the level of fear, it did not contribute to a higher percentage of participants perceiving tinnitus-like sounds in the threat condition. However, higher levels of perceived threat were related to a higher degree of perceived tinnitus unpleasantness. The findings of our study are drawn from a rather homogenous participant pool in terms of age, gender, and educational background, challenging conclusions that are applicable for the general population. Participants generally obtained normophoric scores on independent variables of interest: they were low anxious, low noise-sensitive, and there was little evidence for the presence of subclinical hearing loss. Possibly, there was insufficient variation in scores to find effects.